2016
DOI: 10.1073/pnas.1614759113
|View full text |Cite
|
Sign up to set email alerts
|

Methyltransferase-like protein 16 binds the 3′-terminal triple helix of MALAT1 long noncoding RNA

Abstract: ; reviewed by Brenda L. Bass and Eric M. Phizicky)Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), a cancer-promoting long noncoding RNA, accumulates in cells by using a 3′-triple-helical RNA stability element for nuclear expression (ENE). The ENE, a stem-loop structure containing a U-rich internal loop, interacts with a downstream A-rich tract (ENE+A) to form a blunt-ended triple helix composed of nine U • A-U triples interrupted by a C • G-C triple and C-G doublet. This unique structure promp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
205
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(224 citation statements)
references
References 30 publications
7
205
1
Order By: Relevance
“…However, S. cerevisiae does not encode a METTL16 homolog and, to our knowledge, budding yeast U6 snRNA is not methylated. Moreover, METTL16 is nuclear, consistent with a role in regulation of MAT2A splicing and U6 methylation (Brown et al, 2016). For these reasons, we explored the possibility that METTL16 methylates MAT2A and U6 snRNA.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…However, S. cerevisiae does not encode a METTL16 homolog and, to our knowledge, budding yeast U6 snRNA is not methylated. Moreover, METTL16 is nuclear, consistent with a role in regulation of MAT2A splicing and U6 methylation (Brown et al, 2016). For these reasons, we explored the possibility that METTL16 methylates MAT2A and U6 snRNA.…”
Section: Resultsmentioning
confidence: 79%
“…The C. elegans and A. thaliana SAM synthetase genes have no UACAGAGAA elements, so these phenotypes are likely attributable to loss of U6 snRNA methylation, methylation of an unidentified target(s), or even other unknown functions of METTL16. In fact, while this work was under review, METTL16 was reported to bind a structured 3´-end triple helix structure of the nuclear noncoding MALAT1 RNA, apparently independent of its methyltransferase activity (Brown et al, 2016). The substrate specificities of METTL16 family members suggest that they evolved initially to be rRNA methyltransferases and subsequently were co-opted by eukaryotes to target U6 snRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several questions remain to be answered: for example, does the triple helix structure have additional functions besides regulating RNA stability; what is the function of the tRNA-like structure; does it only provide an RNase P cleavage site to produce lncRNAs with a triple helix 3′-tail. The recent identification of one MALAT1 triplex-interacting protein, RNA methyltransferase-like protein 16 (METTL16), suggests the existence of a class of triple-stranded RNA binding proteins (Brown et al, 2016). Future identification of additional proteins associated with the triple-helix and tRNA-like structures will provide further functional insights.…”
Section: Discussionmentioning
confidence: 99%
“…This binding happens via a triple RNA binding helix element as Brown et al 168 have observed. MALAT1 is a long non coding RNA whose 3' functional motiff plays a role in the cell proliferation, invasion and metastasis in CRC 169 .…”
Section: Dicationmentioning
confidence: 89%